Emotions Evoked from “Too Good at Goodbyes” Song by Sam Smith - Febriana Aminatul Khusna; Sekar Lathifatul Aliyah (Univeristas Negeri Gorontalo, 2020)
Music is one means to express the soul. Sad genre music is one of music with high emotional pressure. High emotional pressure allows triggering emotions in someone who hears it. According to Sloboda and Juslin (2001), the music can induce emotions in its listeners and is perceived by listeners as expressive of emotion. The aim of this study was to investigate the influence of music with the sad genre for emotions from the song